Upaya Pengkondisian Kelas untuk Mendisiplinkan Siswa - Ganjar, Devi (Ta'lim: The Islamic Religious Educational Journal, 2024)
Class conditioning is a fundamental component of learning management aimed at creating an orderly, effective learning environment that supports the development of student discipline. Discipline is not merely understood as compliance with rules, but as students’ ability to manage their behavior, responsibilities, and learning awareness. This article provides a theoretical analysis of various classroom conditioning efforts to cultivate student discipline through a literature-based approach. The findings indicate that effective classroom conditioning requires the integration of preventive strategies, positive reinforcement, humanistic approaches, and the creation of a democratic classroom climate. Various theories—such as behaviorism, social-cognitive theory, and humanistic approaches—offer a strong foundation for understanding that discipline is not simply a repressive action, but a behavioral construction that develops through repeated interactions among students, teachers, rules, and the learning environment. This article asserts that teachers play a central role as classroom managers, motivators, and moral exemplars in fostering discipline through planned, consistent classroom conditioning grounded in pedagogical values.